BEHAVIORAL ECONOMICS AND GREEN ENERGY ADOPTION: A REVIEW OF NUDGES, EXPERIMENTAL EVIDENCE, AND POLICY APPLICATIONS (NeoEcon review, 2026)
This study examines the role of behavioral nudges in fostering green energy adoption, emphasizing experimental evidence and policy implications. Drawing on theories such as Expected Utility Theory, Prospect Theory, and Nudge Theory, the paper explores how psychological and cognitive factors influence energy-related decision-making. Behavioral tendencies such as status quo bias, loss aversion, and social norm adherence are analyzed in their capacity to impede or enhance the adoption of renewable energy technologies. Empirical evidence highlights the efficacy of interventions like green defaults, feedback mechanisms, and competence-boosting strategies in promoting sustainable behaviors. Studies demonstrate significant energy savings through tailored nudges, with persistent effects when interventions account for socio-economic and cultural contexts. Ethical considerations, including transparency and autonomy, are also discussed. The review underscores the potential of combining behavioral insights with economic policies to overcome psychological barriers to green energy adoption. Future research should focus on the scalability of nudges, the integration of emerging technologies, and addressing inequalities to ensure equitable access to renewable energy solutions.
Keywords: behavioral nudges, green energy adoption, prospect theory, nudge theory, expected utility theory, energy policy, psychological barriers